Inflammatory myofibroblastic tumour of the lung manifesting as progressive atelectasis - Verbeke, Jonathan I. M. L.; Verberne, Anja A. P. H.; Den Hollander, Jan C.; Robben, S. G. F. (Pediatric radiology, 1999)
A 6-year-old girl with an inflammatory myofibroblastic tumour of the lung is presented. The radiological features of this lesion are often atypical, as in this case, presenting as progressive atelectasis. The differential diagnosis is extensive and can be difficult, despite modern imaging techniques.